SYNTHESIS AND CHARACTERIZATION OF CYCLOHEXANE-1,3-DIONE DERIVATIVES AND THEIR IN SILICO AND IN VITRO STUDIES ON ANTIMICROBIAL AND BREAST CANCER ACTIVITY - CHINNAMANAYAKAR, RAJA; MR, EZHILARASI; B, PRABHA; M, KULANDHAIVEL (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to evaluate in silico and in vitro anticancer activity for synthesized cyclohexane-1,3-dione derivatives. Methods: The new series of cyclohexane-1,3-dione derivatives were synthesized based on the Michael addition reaction. Further, the structures of the synthesized compounds were confirmed by Fourier-transform infrared spectroscopy, 1H nuclear magnetic resonance (NMR), and 13C NMR spectral data. Then, the in silico molecular docking studies were carried out using AutoDock tool version 1.5.6 and AutoDock version 4.2.5.1 docking program. The antimicrobial activity was carried out using the agar disk diffusion method, and the in vitro anticancer activity was performed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay for the synthesized compound. Results: In silico docking study, compound 5c showed good binding score and binding interactions with selected bacterial proteins and breast cancer protein. Further, compound (5a-5h) was tested for their antimicrobial activity and compound 5c was only tested for anticancer activity (human breast adenocarcinoma 3,4-methylenedioxyamphetamine-MB-231 cell line). Compound 5c was found to be the most active one of all the tested compounds. In the MTT assay compound, 5c showed the LC50 value of 10.31±0.003 μg/ml. In antimicrobial activity, the minimum inhibitory concentration of compound 5c is 2.5 mg/ml. Conclusion: An efficient synthesis of biologically active cyclohexane-1, 3-dione derivatives has been developed.